"Народная археалогія" і данавуковыя ўяўленні аб пахавальных помніках Беларускага Падзвіння ХIV–ХVIII стагоддзяў - Чараўко, В. У. (Мінск : Беларуская навука, 2020)
The scientific study of the funerary monuments of the Belarusian Dvina region of the 14th- 18th centuries was preceded by it’s "folk archeology" - a specific interpretation by the local population. In the traditional society, some late medieval funerary monuments became objects of sacred topography and the material embodiment of the folklore memory of military events. Names like "French cemetery", "Tatar cemetery", "Volotovka", which are mainly designated mounds and hillforts, were also used to name the late medieval burial fields (Glubokoe, Dokshitsy, Polotsk, Shumilino districts). The population of the Belarusian Dvina region encountered late medieval funerary monuments and in damage of burials. Archaeological evidence of this has been found on a number of rural burial fields and urban necropolises of the period studied. Accidental burial damages occurred with the intensive use of burial fields and/or in old, but active cemeteries. On the burial fields near the villages of Kieschino, Zhernosekovo, Dubrovka, the opening of earlier burials was carried out purposefully for the additional burials. Damage to the burials occurred during the construction. In some cases, the damage of burials was due to loss of memory about them. Изучению погребальных памятников Белорусского Подвинья ХIV–ХVIII вв. предшествовала их «народная археология» — специфическая интерпретация местным населением. В традиционном обществе некоторые позднесредневековые погребальные памятники стали объектами сакральной топографии и материальным воплощением фольклорной памяти о военных событиях. Население Белорусского Подвинья сталкивалось с позднесредневековыми погребальными памятниками и при нарушении погребений. Археологические свидетельства этого выявлены на ряде сельских могильников и городских некрополей изучаемого периода. Случайные нарушения погребений происходили при интенсивном использовании могильников и/или на старых, но действующих кладбищах. На могильниках возле деревень Клещино, Жерносеково, Дубровка вскрытие более ранних погребений ...